2015
DOI: 10.1590/1414-431x20154445
|View full text |Cite
|
Sign up to set email alerts
|

Gender, race and socioeconomic influence on diagnosis and treatment of thyroid disorders in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil)

Abstract: Thyroid diseases are common, and use of levothyroxine is increasing worldwide. We investigated the influence of gender, race and socioeconomic status on the diagnosis and treatment of thyroid disorders using data from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil), a multicenter cohort study of civil servants (35-74 years of age) from six Brazilian cities. Diagnosis of thyroid dysfunction was by thyrotropin (TSH), and free thyroxine (FT4) if TSH was altered, and the use of specific medications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 24 publications
3
42
3
3
Order By: Relevance
“…In males (see Table 2) the proportion of hyperthyroidism is 2.7 % which is high compared to females which is 2.5 %. The proportion of hypothyroidism, subclinical hypothyroidism and subclinical hyperthyroidism is high among females as compared to males being 4.6%, 11.3% and 2.2% as compared to that of males being 4.2 %, 7.1 % and 1.8 % respectively which is in accordance to the findings of Olmos 23 and Aquino 24 .…”
Section: Resultssupporting
confidence: 89%
“…In males (see Table 2) the proportion of hyperthyroidism is 2.7 % which is high compared to females which is 2.5 %. The proportion of hypothyroidism, subclinical hypothyroidism and subclinical hyperthyroidism is high among females as compared to males being 4.6%, 11.3% and 2.2% as compared to that of males being 4.2 %, 7.1 % and 1.8 % respectively which is in accordance to the findings of Olmos 23 and Aquino 24 .…”
Section: Resultssupporting
confidence: 89%
“…49 After that, the vast majority of male and female specialists in this area admitted being aware of the WHI results (95.9%), and although 84.6% stated that those results could not be extrapolated to forms of HT other than those evaluated in the study, a significant decrease in prescription was self-reported. 50 Another finding of the ELSA-Brasil study was the inappropriate use of thyroxine by more educated women and those with higher incomes 51 and of benzodiazepines by those with health insurance, 52 and this would appear to support this interpretation of the results and indicate the need for further studies on the quality of the private medical care often used by the more privileged socioeconomic classes in Brazil.…”
Section: Discussionmentioning
confidence: 92%
“…cities. 16 ELSA-Brasil showed that participants with subclinical hyperthyroidism had a 2.5 times greater chance of presenting panic disorder, while those who had subclinical hypothyroidism had a 25% lower frequency of generalized anxiety disorder.…”
Section: Subclinical Thyroid Disordersmentioning
confidence: 99%